The biogas potential of animal manure and its GHG reduction effect in Konya province, Turkey - Karaca, Cengiz (Journal of Environmental Engineering and Landscape Management, 2023)
This study aims to assess the amount of biogas and value of energy produced from animal manure in Konya province. Therefore, the potential of biogas was calculated by considering the number of cattle, broilers, and laying hens. It was calculated that a total of 5.63 million tonnes of animal manure comprising 5.25 million tonnes of cattle manure, 1.07 thousand tonnes of broiler manure, and 382.38 thousand tonnes of laying hen manure could be taken from these animals in the province. 105.67 Mm3 biogas can be produced from the available amount of this manure. It was calculated that electric energy of approximately 266.53 GWhel can be produced from this biogas. Furthermore, greenhouse gas (GHG) emission reduction was calculated to show the environmental benefits of biogas production from animal manure. Upon benefiting from the total of the calculated biogas potential, it was determined that CO2 emission reduction ranging from 1.04–1.57 million tonnes could be provided.